EMPOWERING ADOK TRADITIONAL ART IN ITS POWERLESSNESS - Selvi Kasman (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
Artistry Tradition Adok is part of the cultural asts, refer to the value of (aesthetics), comes from an expression of human desire to the beuty, that is enjoyed with eyes and ears. Interesting things from the performance adok tradisional arts contained on each elements. Music, serves as accompanist in dance movement in adok that use music instruments such as drum that is coated with tiger skin as a membrane-producing sound, people call it as gandang adok; elements of dance that its move is based on the movement of martial arts, danced by men; Other elements are text shaped ABAB rhyme pattern, sang by gandang player. This research use qualitative method for results deskriptif like written or oral from many people and behaviour which observable. The approach directed to background individu in holystic. The problem is that the adok traditional arts is not fully supported by willingness of traditional art is not paralel with the rapid development of all society aspects. Society as the actors are less motivated and incapable to do much things on its consistent maintainance The forms of empowerment are made through coaching toward the actors and performace aspects. They also form the traditional aspects for the benefit of adok traditional art performance package. Therefore, the supporting society have the ability to answer the challenges and maintain art and culture in this area. Because one of a developed society is to have the ability to save and preserve the cultural arts. Through the seminar is one way to give an information about art and culture, in order to be appreciated, enjoyed, loved and it is expected can motivate the community of performers to play their part in its preservation.